2022
DOI: 10.3389/fnagi.2022.877281
|View full text |Cite|
|
Sign up to set email alerts
|

Regional Homogeneity in Patients With Mild Cognitive Impairment: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: ObjectiveTo analyze the potential changes in brain neural networks in resting state functional magnetic resonance imaging (rs-fMRI) scans by regional homogeneity (ReHo) in patients with mild cognitive impairment (MCI).MethodsWe recruited and selected 24 volunteers, including 12 patients (6 men and 6 women) with MCI and 12 healthy controls matched by age, sex, and lifestyle. All subjects were examined with rs-fMRI to evaluate changes in neural network connectivity, and the data were analyzed by ReHo method. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In clinical research, Wu YQ, et al . found that the bilateral inferior temporal gyrus signal was significantly lower in mild cognitive impairment (MCI) patients than that in healthy subjects [ 63 ], indicating that the decreased activity of the bilateral inferior temporal gyrus may be involved in cognitive impairment. The relationship between BOLD changes and AD risk genes (especially APOEε4) has been extensively studied.…”
Section: The Energy Dysmetabolism In Alzheimer’s Disease Brainmentioning
confidence: 99%
“…In clinical research, Wu YQ, et al . found that the bilateral inferior temporal gyrus signal was significantly lower in mild cognitive impairment (MCI) patients than that in healthy subjects [ 63 ], indicating that the decreased activity of the bilateral inferior temporal gyrus may be involved in cognitive impairment. The relationship between BOLD changes and AD risk genes (especially APOEε4) has been extensively studied.…”
Section: The Energy Dysmetabolism In Alzheimer’s Disease Brainmentioning
confidence: 99%